Emotional Regulation in Autism Spectrum Disorders: A New Proposed Model for Regulating Emotions through Parent Education - Mainul Haque (Journal of Global Pharma Technology, 2017)
Autism spectrum disorders (ASD) may affect all spheres of a child’s life. One of the areas of the behavioral spectrum need to be focused is affected. Thus, the study is enthused in impaired emotional regulation (ER) affecting children with ASD. The significance of ER is related to that promoting adaptive behavior in children; indeed, disturbed ER in ASD children leads to emotional and behavioral problems. Commonly children with ASD lack adaptive ER strategies thus they react impulsively and inadequately to emotional stimuli thus it affects their psychological well-being. Though ER in ASD children is intrinsic the nurturing of these children with an understanding of ER can promote better psychological wellbeing. Thus, study objectives to examine a) the impact of ASD on their ER b) the impact of ER on the psychological wellbeing of children with ASD c) To develop awareness among these parents regarding the impact of ER on the psychological wellbeing of their ASD child. d) To propose a new model of parental education about ER and its significance on psychological wellbeing of ASD children. This study takes a base on the keenly examined past evidence on impaired ER in ASD children and its impact on psychological wellbeing. Proposal for aiding ER through parental education has introduced. The conclusion drawn in this study is that the intervention can be more promising with educating parents regarding ER, may help their child to gain maximum from therapeutic intervention. The new proposed model of intervention extends the further scope for research in this regard.Keywords: ASD; Emotional regulation, Parent’s education, Intervention.